PROBLEM SOLVING IN TRANSLATING INDONESIA LEGAL DOCUMENTS TO ENGLISH - Deyani, Christine (Universitas Suryakancana, 2022)
Legal translation is a translation made for interest and has a legal nature, an example of legal translation is the translation of a notary deed. This translation includes institutional translation because it has a close relationship in culture and is quite difficult to translate by ordinary people. Therefore, here the author will look for several solutions that can be used by other translators when they want to translate the same legal text. Here the author finds several techniques that can be used in translating legal texts and some online references that can be used if you find an equivalent or term in the law. There are several strategies used by the author when translating notarial deed documents, such as the use of literal translation, adaptive translation, calque translation, official translation, cultural equivalence, transference, and various online references that are used to support better translation results.